Regulatory mechanism of exogenous myo-inositol improving high temperature stress tolerance of tomato seedlings - CHEN Yan; HAN Liyuan; DU Zilong; ZHU Dongxing; ZHU Weimin; ZHANG Yingying (Xibei zhiwu xuebao)
[Objective] Studing the effect of exogenous myo-inositol on the physiological and biochemical indexes of tomato seedlings and the molecular mechanism of tolerance to high temperature stress will provide a theoretical basis for the improvement of heat resistance of tomato. [Methods] Tomato variety ‘NRP20- 7’ was used as the test material, and water and myo-inositol were sprayed separately at normal temperature and high temperature, respectively. The phenotypic changes under treatments were analyzed by hyperspectral imaging, and the physiological indexes of each treatment group were analyzed. The expression of heat responsive genes, antioxidant, and ABA-related genes were analyzed by qRT-PCR. [Results] 20 mmol/L myo-inositol treatment could effectively alleviate the damage of high temperature stress on tomato seedlings, reduce the heat damage index of tomato leaves, increase the maximum photochemical efficiency (Fv/Fm), and significantly increased the content of photosynthetic pigments. Exogenous myo-inositol increased proline and soluble sugar contents and peroxidase activity, and decreased malondialdehyde, hydrogen peroxide, and superoxide anion contents in tomato seedlings at high temperature. Exogenous myo-inositol increased the expression of heat response genes, antioxidant-related genes, ascorbic acid synthesis genes, and decreased the expression of heat shock protein genes. In addition, exogenous myo-inositol responded to high temperature stress by regulating abscisic acid synthesis and signaling pathways to regulate the level of ABA in tomato seedlings. [Conclusion] Exogenous myo-inositol enhances tomato tolerance to high temperature stress by regulating complex biological processes in plants.